Basic Literacy Difficulties During the School Transition: A Cognitive-Affective Model Based on Educational Psychology - Hamilaturroyya Hamilaturroyya; Mar'atus Sholikah; Ahmad Syarif Hidayatullah; Zaenal Abidin; Uswatun Khasanah (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
Basic literacy attainment among Indonesian junior high school students has remained stagnant despite more than a decade of policy intervention, indicating that prevailing approaches have not addressed the underlying mechanisms. The cognitive and affective dynamics shaping literacy trajectories during the elementary-to-secondary transition specifically remain empirically underexplored. This study examined how adolescents with high digital media exposure experience basic literacy difficulties during this transition, identified the cognitive and affective factors involved, and analyzed how learning conditions sustain or disrupt the resulting cycle. A single qualitative case study was conducted with 18 informants 12 students, 5 teachers, and 1 principal at an urban public junior high school in Central Java. Data were collected through semi-structured interviews, five classroom observations, and document analysis, and were analyzed using the interactive model of thematic data analysis. Trustworthiness was established through source and method triangulation, member checking, peer debriefing, and audit trails. Findings revealed that the majority of students exhibited persistent reading comprehension failure under independent task conditions, accompanied by pervasive affective barriers including reading anxiety, avoidance behavior, and constrained written expression that systematically curtailed literacy practice. Teacher-centered oral instruction and unstructured digital media consumption were identified as the primary environmental conditions sustaining these patterns. Together, these elements constitute a self-reinforcing cycle in which limited cognitive engagement amplifies negative affect, which in turn suppresses literacy exposure. This study proposes the Cognitive-Affective Coupling Model in Literacy Transition (CACM-LT) and argues that effective interventions must integrate explicit cognitive instruction, emotionally supportive pedagogical environments, and coherent institutional policy